Synthesis, α-glucosidase inhibitory and molecular docking studies of prenylated and geranylated flavones, isoflavones and chalcones. Issue 20 (15th October 2015) - Sun, Hua; Li, Yashan; Zhang, Xiaoting; Lei, Yanan; Ding, Weina; Zhao, Xue; Wang, Haomeng; Song, Xiaotong; Yao, Qingwei; Zhang, Yongmin; Ma, Ying; Wang, Runling; et al.
Graphical abstract: Abstract: Three series of prenylated and/or geranylated flavonoids were synthesized and evaluated for their α-glucosidase inhibitory activity. The 3′, 5′-digeranylated chalcone (16 ) was identified as a new α-glucosidase inhibitor whose activity (IC50  = 0.90 μM) was 50-fold more than that of acarbose (IC50  = 51.32 μM). Molecular docking studies revealed the existence of strong hydrophobic interaction and H-bonding between compound16 and α-glucosidase's active site. The inhibitory mode analysis showed that16 exhibited a competitive inhibitory mode.